Quantification of circulating cell-free plasma DNA and endothelial gene RNA in patients with burns and relation to acute thermal injury. - Fox, A; Gal, S; Fisher, N; Smythe, J; Wainscoat, J; Tyler, M; Watt, S; Harris, A (2008)
BACKGROUND: Major burn represents a multi-system insult to the human body. Despite improvements in mortality and morbidity, reliable predictors of outcome are lacking. Raised levels of cell-free nucleic acids have been detected in various pathological processes including burns. We quantified circulating nucleic acids as potential objective measures of burn severity with predictive and prognostic value. METHODS: Expression of endothelial specific cell-free mRNA and cell-free DNA were measured in plasma of 19 burn patients at days 1-3 and week 10 following acute thermal injury and in 19 healthy controls by real-time quantitative PCR. RESULTS: Expression of endothelial specific mRNA was higher in burn patients compared to controls (p<0.001). DNA levels were significantly higher in the burn population in the first 48 h following injury. Plasma RNA and DNA levels related to %TBSA burn in the first 24h and to the levels of circulating endothelial progenitor cells. CONCLUSIONS: We show that plasma levels of endothelial specific mRNA and DNA are elevated acutely following burns, and relate to severity in terms of %TBSA burnt.